Left ventricular outflow tract velocity time integral in hospitalized heart failure with preserved ejection fraction - Omote, Kazunori (ESC Heart Fail, 2019)
AIMS: The prognostic implication of left ventricular outflow tract velocity time integral (LVOT‐VTI) on admission in hospitalized heart failure with preserved ejection fraction (HFpEF) patients has not been determined. We sought to investigate whether LVOT‐VTI on admission is associated with worse clinical outcomes in hospitalized patients with HFpEF. METHODS AND RESULTS: We studied consecutive 214 hospitalized HFpEF patients who had accessible LVOT‐VTI data on admission, from a prospective HFpEF‐specific multicentre registry. The primary outcome of interest was the composite of all‐cause death and readmission due to heart failure. During a median follow‐up period of 688 (interquartile range 162–810) days, the primary outcome occurred in 83 patients (39%). The optimal cut‐off value of LVOT‐VTI for the primary outcome estimated by receiver operating characteristic analysis was 15.8 cm. Lower LVOT‐VTI was significantly associated with the primary outcome compared with higher LVOT‐VTI (P = 0.005). Multivariable Cox regression analyses revealed that lower LVOT‐VTI was an independent determinant of the primary outcome (hazard ratio 0.94, 95% confidence interval 0.91–0.98). In multivariable linear regression, haemoglobin level was the strongest independent determinant of LVOT‐VTI among clinical parameters (β coefficient = −0.61, P = 0.007). Furthermore, patients with lower LVOT‐VTI and anaemia had the worst clinical outcomes among the groups (P < 0.001). CONCLUSIONS: Lower admission LVOT‐VTI was an independent determinant of worse clinical outcomes in hospitalized HFpEF patients, indicating that LVOT‐VTI on admission might be useful for categorizing a low‐flow HFpEF phenotype and risk stratification in hospitalized HFpEF patients.